Decentralized agent-based electronic marketplace supply chain ecosystem - Gumzej, Roman (Array, 2018)
Electronic marketplaces have become an essential part of the business to business e-commerce. Supply chain concept is fully taking advantage of using the network effects in electronic marketplaces due to augmented added value from each participant. However, highly desirable network effects lead to one company monopoly over the whole marketplace. To prevent this effect, authors are proposing and devising a decentralized agent-based electronic marketplace for supply chain ecosystem. The goal of our research is to improve overall supply chain service quality by allowing companies’ agents to evaluate the service quality of their partners through the history of their transactions. Consequently, since in their procurement activities more informed decisions are being made instantaneously, continuously and autonomously at each node of a supply chain, supply chain service quality is being improved along the whole supply chain.